Soil-site suitability for Indian mustard in Jamnagar district of Gujarat (Journal of Oilseed Brassica, 2026)
Nine typical pedons of soils of Jamnagar district in Saurashtra region, Gujarat were evaluated for their suitability to Indian mustard [Brassica juncea (L.) Czern & Coss.] cultivation limitations i.e. number and intensity of limitations. The study suggests that Indian mustard is moderately suitable in soils of Pedon P4, P5 and P9 but marginally suitable in soils of Pedon P1, P2, P6 and P7. However, the soils of Pedon P3 and P8 seems to be not suitable for Indian mustard cultivation. Soil depth, drainage, topography, and sodicity are the major limitations for crop growth in most of the soils of Jamnagar district. Results showed that the soil suitability classes can be improved if the correctable limitations (soil depth and drainage characteristics) are altered through soil amelioration measures.